"His Dominion" and the "Yellow Peril" : protestant missions to the Chinese immigrants in Canada, 1859-1967 - Wang, Jiwu, 1956-; Canadian Corporation for Studies in Religion (Waterloo, Ont. : Published for the Canadian Corp. for Studies in Religion/Corporation canadienne des Sciences religieuses by Wilfrid Laurier University Press, 2006)
"A history of Chinese immigrants' encounter with Canadian Protestant missionaries, "His Dominion" and the "Yellow Peril": Protestant Missions to Chinese Immigrants in Canada, 1859-1967, analyzes the evangelizing activities of missionaries and the role of religion in helping Chinese immigrants affirm their ethnic identity in a climate of cultural conflict." "Jiwu Wang argues that, by working toward a vision of Canada that espoused Anglo-Saxon Protestant values, missionaries inevitably reinforced popular cultural stereotypes about the Chinese and widened the gap between Chinese and Canadian communities. Those immigrants who did embrace the Christian faith felt isolated from their community and their old way of life, but they were still not accepted by mainstream society." "Wang documents the methods used by the missionaries and the responses from the Chinese community, noting the shift in approach that took place in the 1920s, when the clergy began to preach respect for Chinese ways and sought to welcome them into Protestant-Canadian life."--Jacket.
Includes bibliographical references (pages 171-180) and index.
Print version record.
Master record variable field(s) change: 082
Keywords: Chinese -- Missions -- Canada -- History; Protestant churches -- Missions -- Canada -- History; Chinese -- Canada -- Religion -- History; Chinese -- Canada -- Religion; Chinois -- Missions -- Canada -- Histoire; Églises protestantes -- Missions -- Canada -- Histoire; Chinois -- Canada -- Religion -- Histoire; RELIGION -- Christian Ministry -- Missions; Chinese -- Missions; Chinese -- Religion; Protestant churches -- Missions; Canada; Electronic books; History